Impact of Lending Interest Rate on Profitability: Evidence from Commercial Banks in Sri Lanka - Kirushanthy, T.; Balagobei, S. (South Eastern University of Sri Lanka, 2020)
Interest rate is one of the important elements in the lending decision process of Commercial Banks. Commercial Banks are independent business entities that set their own lending rates. The lending interest rate is the percentage of the loan amount that the lender charges to lend money. The aim of this study is to investigate the impact of lending interest rate of Commercial Banks in Sri Lanka. The analysis of data was based on a sample of 28 Commercial Banks. The study utilized secondary data which were collected from annual reports of Commercial Banks in Sri Lanka over the period of 2014 to 2018. Models used in the study were: pooled OLS model, fixed effects model and random effects model. This study has used ‘profitability’ measured by return on assets and return on equity as dependent variable, while the explanatory variable is lending interest rate. The study was conducted by using the techniques of correlation and regression. The estimated results reveal that lending interest rate has a significant positive impact on profitability measured by return on assets (ROA). The management of Commercial Banks also need to develop polices and investment sources that diversify income.
Keywords: Lending interest rate; Profitability; Return on assets